Sustainable Environmental Law - Lubogo, Isaac Christopher (Jescho Publishing House, 2022)
For the worldwide goal of preventing climate change while sustaining economic growth and permitting living standards to rise, meeting present and future energy demands sustainably is a crucial challenge. For health care, education, and economic development, it is crucial to have access to affordable, reliable energy, especially electricity. 790 million people in developing nations will not have access to electricity by 2020, and about 2.6 billion will cook with harmful fuels. Most of the United Nations 2030 Sustainable Development Goals, which address topics like gender equality and climate action, may be achieved by increasing energy availability in the least developed nations and making energy cleaner. By 2030, all people must have access to "cheap, dependable, sustainable and contemporary energy for all," including access to electricity and facilities for clean cooking.
Keywords: SDGS; Environmental Law; Uganda